2015
DOI: 10.3889/oamjms.2015.081
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A and Ghrelin Levels in Children with End Stage Renal Disease and the Effect of a Single Hemodialysis Session on Them

Abstract: BACKGROUND:Fetuin-A and ghrelin have been implicated in cardiovascular diseases and mortality among end stage renal disease patients. The exact mechanisms have not been fully elucidated. There is robust data supporting an association between ghrelin and various cardiovascular conditions, and some common processes such as inflammation, oxidative stress, and endoplasmic reticulum stress have been implicated.AIM:This study was conducted to assay serum fetuin-A and ghrelin in chronic renal failure pediatric patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A study by Shouman et al (32), which investigated SF-A levels in hemodialysis patients, showed that pre-dialysis SF-A levels were higher in pediatric hemodialysis patients compared to healthy subjects. Furthermore, they showed a significant decrease in SF-A levels after a single session of hemodialysis (33). In another study by Kirkpantur et al (34), SF-A levels were reported to be associated with coronary artery calcification and the bone mineral density of recipients of maintenance hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Shouman et al (32), which investigated SF-A levels in hemodialysis patients, showed that pre-dialysis SF-A levels were higher in pediatric hemodialysis patients compared to healthy subjects. Furthermore, they showed a significant decrease in SF-A levels after a single session of hemodialysis (33). In another study by Kirkpantur et al (34), SF-A levels were reported to be associated with coronary artery calcification and the bone mineral density of recipients of maintenance hemodialysis.…”
Section: Discussionmentioning
confidence: 99%